Lysosome-related organelles orchestrate guanine crystal formation in pigment cells - Anna Gorelick-Ashkenazi; Yuval Barzilay; Tali Lerer-Goldshtein; Tsviya Olender; Zohar Eyal; May Glaser; Yonatan Broder; Nadav Mishol; Rachael Deis; Merav Kedmi; Dvir Gur (Proceedings of the National Academy of Sciences, 2026)
Iridosomes, the guanine crystal-forming organelles of pigment-producing iridophores, are among the most versatile, visually striking yet mechanistically uncharacterized organelles in vertebrate biology. Lysosome-related organelles (LROs) support cell type–specific functions by adapting endolysosomal pathways for specialized roles. Here, we show that iridosomes represent a subtype of LROs. Using transcriptomic profiling of zebrafish iridophores, CRISPR-Cas9-mediated gene disruption, and cryogenic transmission electron microscopy, we define the molecular program underlying iridosome biogenesis. Iridosomes have evolved unique adaptations for crystal growth while retaining core features of other LROs. Key regulators, including Rab32a, Ap3m2, and Hps5, are essential for crystal formation, with gene knockouts causing reduced crystal number, altered morphology, and distinct maturation defects. We further identify hallmark LRO features in iridosomes, including intraluminal vesicles and pH-regulated developmental transitions. Cross-species transcriptomic analysis confirms that iridosomes share an LRO signature across vertebrates, including teleost fish and reptiles, suggesting ancient evolutionary origins. These findings establish iridosomes as crystalline LROs and as a model for investigating how cells construct structurally specialized organelles through coordinated trafficking and crystallization, with implications for LRO evolution and human disease.